Role of CXCR3 Ligands in IL-7/IL-7Rα-Fc mediated antitumor activity in Lung Cancer - Andersson, Åsa (2011)
PURPOSE: We evaluated the utility of chimeric γc homeostatic cytokine, IL-7/IL-7Rα-Fc, to restore host APC and T cell activities in lung cancer. EXPERIMENTAL DESIGN: Utilizing murine lung cancer models we determined the antitumor efficacy of IL-7/IL-7Rα-Fc. APC, T cell, cytokine analyses, neutralization of CXCL9, CXCL10 and IFNγ were performed to evaluate the mechanistic differences in the antitumor activity of IL-7/IL-7Rα-Fc in comparison to controls. RESULTS: IL-7/IL-7Rα-Fc administration inhibited tumor growth and increased survival in lung cancer. Accompanying the tumor growth inhibition were increases in APC and T cell activities. In comparison to controls, IL-7/IL-7Rα-Fc treatment of tumor bearing mice led to increased: i) levels of CXCL9, CXCL10, IFNγ, IL-12 but reduced IL-10 and TGFβ, ii) tumor macrophage infiltrates characteristic of M1 phenotype with increased IL-12, iNOS but reduced IL-10 and arginase, iii) frequencies of T and NK cells, iv) T cell activation markers CXCR3, CD69 and CD127,(low) v) effector memory T cells and vi) T cell cytolytic activity against parental tumor cells. IL-7/IL-7Rα-Fc treatment abrogated the tumor induced reduction in splenic functional APC activity to T responder cells. The CXCR3 ligands played an important role in IL-7/IL-7Rα-Fc mediated antitumor activity. Neutralization of CXCL9, CXCL10 or IFNγ reduced CXCR3 expressing activated T cells infiltrating the tumor and abrogated IL-7/IL-7Rα-Fc mediated tumor growth inhibition. CONCLUSIONS: Our findings demonstrate that IL-7/IL-7Rα-Fc promotes afferent and efferent antitumor responses in lung cancer.